Analisis Faktor Faktor Yang Berhubungan dengan Kepatuhan Penerapan Protokol Kesehatan di Ditpolairud Polda Sumatera Selatan - Redno Eka Wijaya (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2021)
Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). The COVID-19 pandemic that was discovered at the end of December 2019 killed hundreds of thousands of people around the world. In addition to taking many victims, this pandemic has also created an economic crisis. Increase the surge in unemployment and poverty. Efforts to maintain public health and prevent more and more victims and to restore the economy, the government applies health protocol discipline. The spread of covid 19 can't be stopped easily, because the mutation process is so fast and now a new variant appears. This study aims to determine the factors related to compliance with the application of health protocols at the Ditpolairud Polda Sumsel. As well as knowing whether there is a relationship between members of the Directorate of Polair Compliance with the Implementation of Health Protocols at the Dit Pol Air Polda Sumsel. The data used in this study came from the DIt Polairud clinic of the South Sumatra Police. From the results of this study, it can be concluded that the attitude variable has the most influential relationship in Compliance with the Implementation of the Covid 19 Health Protocol at the Dit Pol Air Polda Sumsel 2021 because it has a p value = 0.000, and an Odd Ratio or OR 13,393, which means that the respondent has a good attitude. 13,393 times more compliant with the COVID-19 health protocol.